(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the specifics and role of tolerance in the society and culture, promotion of tolerance functions in a modern society and the influence of socio-cultural tolerance factors on the social, cultural communication, area of personal communication, formation of social values, spiritual and political culture. The article reveals the social psychological foundations of tolerant behavior, factors and parameters of tolerant communication. Conclusions about tolerance as an integral personality characteristic and contents of cultural communication are made. Tolerance is presented as an essential parameter of identity formation and socialization. Key words: tolerance, intolerance, culture, cultural tolerance, religion, religious tolerance, politics, society, spirituality, conflicts, civilization, communication, identity, values, globalization, person.